2016
DOI: 10.1177/1757743815624117
|View full text |Cite
|
Sign up to set email alerts
|

Remaking the elite university: An experiment in widening participation in the UK

Abstract: This article analyses and critiques the discourse around widening participation in elite universities in the UK. One response, from both university administrators and academics, has been to see this as an 'intractable' problem which can at best be ameliorated through outreach or marginal work in admissions policy. Another has been to reject the institution of the university completely, and seek to set up alternative models of autonomous higher education. The article presents a different analysis in which the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
(9 reference statements)
0
11
0
7
Order By: Relevance
“…As purveyors of 'high standards' and merit-based entry procedures (Warikoo & Fuhr, 2014), highly selective universities in the UK have been criticised for taking a deficit approach to nontraditional students (Thompson, 2019) and for explaining their absence as due to their inability to meet the high entry grade requirements, their poor choice of A-level subjects and/or a general lack of ambition and aspiration (Archer, 2007;McLellan, 2016). Many selective institutions mobilise a rhetoric of diversity in their widening participation efforts.…”
Section: Widening Participation In Elite Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As purveyors of 'high standards' and merit-based entry procedures (Warikoo & Fuhr, 2014), highly selective universities in the UK have been criticised for taking a deficit approach to nontraditional students (Thompson, 2019) and for explaining their absence as due to their inability to meet the high entry grade requirements, their poor choice of A-level subjects and/or a general lack of ambition and aspiration (Archer, 2007;McLellan, 2016). Many selective institutions mobilise a rhetoric of diversity in their widening participation efforts.…”
Section: Widening Participation In Elite Universitiesmentioning
confidence: 99%
“…The twenty English Russell Group universities responded to increased government pressure to widen access by committing £265 million to widening participation activities in the 2019/20 academic year (Russell Group, 2019). However, elite universities have been criticized for adopting a 'deficit approach' in their discourse around diversity and inclusion and hence towards students recruited through such schemes (Archer, 2007;Thompson, 2019), and viewing them as lacking the required academic skills and attributes (Archer, 2007;Gibson et al, 2016;McLellan, Pettigrew & Sperlinger, 2016). Research has shown that some WP students who enter elite institutions feel 'out of place' in academic, social and recreational spaces (Reay, Crozier & Clayton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of the interview data resulted in identification of some core elements of an anchor institution model needed to effectively widen participation in higher education, which are now briefly summarised to show how central student perspectives are to the model. The "anchor institution" approach rests on an understanding of widening participation as pedagogy rather than process (McLellan et al 2016). This includes the design of teaching, course structures and support mechanisms to accommodate students' needs and dispositions.…”
Section: An "Anchor Institution" Model For Widening Participationmentioning
confidence: 99%
“…These educational reforms challenged selection and recruitment processes that had historically seen low income families, males and mature married females excluded from OT; reinforcing the image it was for White, middle-class females (Yates, 1996). Despite a long and clear history of debate, calls for improvement and UK governmental plans to improve access and attainment gaps, certain student groups across socioeconomics, geography, disability and ethnicity, continue to be underrepresented in HE (McLellan et al, 2016; Office for Students, 2019). Similarly, over several decades, the OT community has called for action, to diversify student and workforce populations that mirror the profession’s increasingly diverse service user populations (Atwal, 2021; Colaianni et al, 2022; Ford et al, 2021; Taylor, 2007).…”
Section: Introductionmentioning
confidence: 99%